Overexpression of ThMYC4E Enhances Anthocyanin Biosynthesis in Common Wheat - Zhao, Shuo (Int J Mol Sci, 2019)
The basic helix-loop helix (bHLH) transcription factor has been inferred to play an important role in blue and purple grain traits in common wheat, but to date, its overexpression has not been reported. In this study, the bHLH transcription factor ThMYC4E, the candidate gene controlling the blue grain trait from Th. Ponticum, was transferred to the common wheat JW1. The positive transgenic lines displayed higher levels of purple anthocyanin pigments in their grains, leaves and glumes. Stripping the glumes (light treatment) caused white grains to become purple in transgenic lines. RNA-Seq and qRT-PCR analysis demonstrated that the transcript levels of structural genes associated with anthocyanin biosynthesis were higher in transgenic wheat than the wild-type (WT), which indicated that ThMYC4E activated anthocyanin biosynthesis in the transgenic lines. Correspondingly, the anthocyanin contents in grains, roots, stems, leaves and glumes of transgenic lines were higher than those in the WT. Metabolome analysis demonstrated that the anthocyanins were composed of cyanidin and delphinidin in the grains of the transgenic lines. Moreover, the transgenic lines showed higher antioxidant activity, in terms of scavenging DPPH radicals, in the ethanol extracts of their grains. The overexpression of ThMYC4E sheds light on the traits related to anthocyanin biosynthesis in common wheat and provide a new way to improve anthocyanin content.